2020
DOI: 10.1002/anie.201915895
|View full text |Cite
|
Sign up to set email alerts
|

Acetylene as a Dicarbene Equivalent for Gold(I) Catalysis: Total Synthesis of Waitziacuminone in One Step

Abstract: The gold(I)‐catalyzed reaction of acetylene gas with alkenes leads to (Z,Z)‐1,4‐disubstituted 1,3‐butadienes and biscyclopropanes depending on the donor ligand on gold(I). Acetylene was generated in situ from calcium carbide and water in a user‐friendly procedure. Reaction of acetylene with 1,5‐dienes gives rise stereoselectively to tricyclo[5.1.0.02,4]octanes. This novel double cyclopropanation has been applied to the one step total synthesis of the natural product waitziacuminone from acetylene and geranyl a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…28 The Echavarren group recently developed a most impressive Au(I)-catalyzed bis-cyclopropanation of geranyl acetone 61 (Scheme 12), in which acetylene gas itself (generated in situ from calcium carbide) serves as the substrate. 29 This cascade affords the tricyclo[5.1.0.0 2,4 ]octane natural product waitziacuminone in a single step, and in terms of atom and step economy constitutes a 'near-ideal' synthesis. 3 Stereoselectively generating four C-C bonds and three rings, the reaction proceeds via initial cyclopropanation of 61 by the h 2 -acetylene gold(I) complex 62 to form cyclopropyl gold carbene 63; the site-selectivity and diastereoselectivity of this step was determined computationally to favour the terminal alkene by ~1.6 kcal mol -1 .…”
Section: Transition Metal-catalyzed Cascadesmentioning
confidence: 99%
“…28 The Echavarren group recently developed a most impressive Au(I)-catalyzed bis-cyclopropanation of geranyl acetone 61 (Scheme 12), in which acetylene gas itself (generated in situ from calcium carbide) serves as the substrate. 29 This cascade affords the tricyclo[5.1.0.0 2,4 ]octane natural product waitziacuminone in a single step, and in terms of atom and step economy constitutes a 'near-ideal' synthesis. 3 Stereoselectively generating four C-C bonds and three rings, the reaction proceeds via initial cyclopropanation of 61 by the h 2 -acetylene gold(I) complex 62 to form cyclopropyl gold carbene 63; the site-selectivity and diastereoselectivity of this step was determined computationally to favour the terminal alkene by ~1.6 kcal mol -1 .…”
Section: Transition Metal-catalyzed Cascadesmentioning
confidence: 99%
“…Recently, Echavarren's group (Scharnagel et al, 2020) reported a gold(I)-catalyzed double cyclopropanation using acetylene as a unique dicarbene equivalent ( Figure 1B). A 3/6/3 fused tricyclic scaffold can be formed in a diastereoselective way by employing 1,5-dienes as substrates, which can be used for one step total synthesis of waitziacuminone from geranyl acetone.…”
Section: Construction Of Polycyclic Carbocyclesmentioning
confidence: 99%
“…Acetylene acting as a dicarbene analog has been successfully demonstrated recently. [ 35 ] Calcium carbide reacts with stilbenes 25 giving dienes 26 in moderate yields or bis‐cyclopropanes 27 in good yields; the reaction is catalyzed by gold (Scheme 11). The structure of the product depends on the catalyst: the use of N‐heterocyclic carbene ligands favors formation of bis‐cyclopropanes 27 .…”
Section: A Map Of Calcium Carbide Synthetic Transformationsmentioning
confidence: 99%
“…Under these conditions, 1,5‐dienes are transformed into waitziacuminone derivatives in good to excellent yields. [ 35 ] This methodology has a good perspective for further development using gold‐activated acetylene as a dicarbene equivalent.…”
Section: A Map Of Calcium Carbide Synthetic Transformationsmentioning
confidence: 99%